ACTIVIDAD TURÍSTICA Y SU CONTRIBUCIÓN AL EMPLEO JUVENIL EN BABAHOYO - MURILLO BAZAN, NAHIN ISAIAS (2024)
The contribution to youth employment provided by tourism activity is of great importance for the economy of a country to increase the number of economically active population, generating better standards of living for the population, therefore in this research the objective was established to analyze the contribution of tourism activity to youth employment to demonstrate the opportunities and challenges of both young people and employers. A quantitative approach methodology was implemented in which statistical data is collected about the youth employment rate in Babahoyo. The city's tourism companies were taken as the target population; the sample was determined by convenience in accordance with the motivations for participation of fifteen establishments interested in contributing to this research. Which they expressed through a survey that contained questions about the number of employees they have and how many of them are young, obtaining a total of sixteen workers between eighteen and twenty-five years of age, with such a low number of youth participation within the tourism activity, it is recommended that the academy look for tourism companies in Babahoyo that want to participate in the internship and pre-professional internship program, and that the municipal authorities give more promotion to public tourist attractions such as: the boardwalk, cultural events and open houses in the To expose the culture of the city, it is recommended that tourism business owners implement training programs for their employees to improve the provision of services in order to attract more clients, thus increasing the need to generate more jobs that include young people. to maintain the quality of the services offered.